Perancangan Perancangan Alat Distilasi Air Mawar : Perancangan Alat Distilasi Air Mawar - Siswantoro , A. Teguh; Kurnianingtyas, Chandra Dewi; Widiatma , Imanuel Wahyu Putra (Jurnal Atma Inovasia, 2024)
The Sapuangin Merapi area, Klaten Regency is a buffer village. The Sapuangin area is under the supervision of the Mount Merapi National Park Office. The Sapuangin area includes the Tegalmulyo Village area, Kemalang District, Klaten Regency. Tegalmulyo Village is located close to Mount Merapi, so this village has good natural resources, fertile soil and cool air. Local village people plant roses in fields. Every day, roses are harvested with a yield of 50 kg. Roses are sold to collectors every day. The price of roses sold is adjusted to the price of roses on the market on that day. The price of roses can change at any time according to market mechanisms. In certain months it is related to the tradition of visiting graves. The price of roses can be very high due to high demand. On the other hand, in normal months the market demand for roses is very low, while the rose harvest remains abundant, so the price of roses becomes very cheap, and sellers find it difficult to market them. To increase/maintain the economic value of roses, the Atma Jaya Yogyakarta University (UAJY) community service team provide training and provide equipment for processing rose flowers into rose water. Processing rose flowers into rose water uses a distillation process. The UAJY Faculty of Industrial Technology community service team designed the distillation equipment. The result of distilling rose water has many benefits and higher economic value, so it can increase the income of local people when the price of roses is cheap.